Sudden Cardiac Death in the Young and Athletes Text Atlas of Pathology and Clinical Correlates - Thiene, Gaetano; Corrado, Domenico; Basso, Cristina (Springer Milan : Imprint: Springer, 2016)
This text atlas focuses on the pathology and molecular genetics of sudden cardiac death in the young and in athletes, presenting the state of the art in the field as the basis for development and implementation of more effective prevention strategies, including, ultimately, molecular therapy that will cure the underlying biological defect. A wealth of high-resolution color images, accompanied by clear supporting text, are presented to document the anatomic pathology of the cardiac diseases most frequently responsible for sudden cardiac death in this population, including coronary artery diseases, cardiomyopathies, myocarditis, valve diseases, conduction system abnormalities, congenital heart diseases, and ion channel diseases. The role of the molecular autopsy in overcoming the limitations of morphological investigations and offering new insights and avenues for prevention is explained. The approach is, however, interdisciplinary, with close attention also to epidemiologic and clinical aspects. The authors draw throughout on their experience gained over 30 years in the course of a prospective study carried out in the Veneto Region, North East Italy. This text atlas will be of great value not only for cardiologists but also for geneticists, sports physicians, and residents in cardiology and pathology.